Geographical Analysis of Sanitation Workers in the Urban District of Kut (Journal of the College of Education for Women, 2023)
Cleaning is one of the services provided by the state and its ad hoc institutions. Every developed country is clean due to the good planning and attention given to the staff of all municipalities and service institutions. Beside, the attention paid to this sector is considered one of the windows to maintain the states’ aesthetics. If janitors stop disposing of all the discarded wastes, the result will be having big piles of waste, affecting accordingly the health and safety of its citizens and the aesthetics of the areas. The janitors and those responsible for them are those that the state must take care of because of their importance to the state in general and to the province in particular. The importance of the research comes from the fact that the janitors are an integral part of the urban population of kut district. They further have a positive role in the removal of waste within the district, and because they are a neglected segment, the researcher has decided to address them in the present research because of the  importance of the topic. The study has thus adopted the general approach in geography, i.e., the descriptive analytical approach to show detailed data on the sanitation workers. The study has mainly concluded that most of the janitors are of illiterate level of education and the lowest level of education is a preparatory school or above. Moreover, their income is of a low level, and so they live in slums, and some of them have no housing owned by them.